Standard procedures for the diagnostic pathway of sleep‐related epilepsies and comorbid sleep disorders: an EAN, ESRS and ILAE‐Europe consensus review. (21st September 2020) - Nobili, L.; de Weerd, A.; Rubboli, G.; Beniczky, S.; Derry, C.; Eriksson, S.; Halasz, P.; Högl, B.; Santamaria, J.; Khatami, R.; Ryvlin, P.; Rémi, J.; et al.
Abstract : Background and purpose: Some epilepsy syndromes (sleep‐related epilepsies, SREs) have a strong link with sleep. Comorbid sleep disorders are common in patients with SRE and can exert a negative impact on seizure control and quality of life. Our purpose was to define the standard procedures for the diagnostic pathway of patients with possible SRE (scenario 1) and the general management of patients with SRE and comorbidity with sleep disorders (scenario 2). Methods: The project was conducted under the auspices of the European Academy of Neurology, the European Sleep Research Society and the International League Against Epilepsy Europe. The framework entailed the following phases: conception of the clinical scenarios; literature review; statements regarding the standard procedures. For the literature search a stepwise approach starting from systematic reviews to primary studies was applied. Published studies were identified from the National Library of Medicine's MEDLINE database and Cochrane Library. Results: Scenario 1: Despite a low quality of evidence, recommendations on anamnestic evaluation and tools for capturing the event at home or in the laboratory are provided for specific SREs. Scenario 2: Early diagnosis and treatment of sleep disorders (especially respiratory disorders) in patients with SRE are likely to be beneficial for seizure control. Conclusions: Definitive procedures for evaluating patients with SRE are lacking. Advice is provided that could be of help for standardizing and improving the diagnostic approach of specific SREs. The importance of identifying and treating specific sleep disorders for the management and outcome of patients with SRE is underlined.